Kemampuan Menyusun Skripsi Ditinjau Dari Tingkat Literasi Media Informasi - Yulia Yulia; Wawan Krismanto; Hasnah Hasnah (Prodi PGSD FIP UNM, 2017)
The world community agreed on the importance of information media literacy for the world's population, not least the students, to the era of media saturated world. The general objective of this study is determine the level of information media literacy students of Primary School Teacher Education, Faculty of Education, University of Makassar, especially at UNM Campus V Parepare. Interest in particular to determine: 1) The influence of the level of media literacy in the student information on the ability of writing his thesis, 2) Influence of gender on the ability of a student thesis, and 3) Interaction between the level of media literacy and sex of the student information with the ability thesis. This study uses causal comparative (ex post facto) with a 2x2 factorial design. Subjects were students who complete the thesis in the second semester 2015/2016. Collecting data using questionnaires and documentation study. Test the hypothesis using analysis of variance (ANOVA) with a two-way interaction. The results showed that the average score of the level of media literacy of information the students were in the category of basic level and only 18% that are at an advanced level that indicates a high access of information media among students of Primary School Teacher Education, Faculty of Education, University of Makassar, especially at UNM Campus V Parepare has not been matched by the good ability of information media literacy. Hypothesis test results show: 1) There is the influence of the level of media literacy in the student information on the ability of writing his thesis, 2) there is no influence of the sex of the students in the ability of his thesis, and 3) there is interaction between the level of media literacy information and gender with the ability of students in thesis.Keywords: information media literacy; information literacy; media literacy; ability of writing thesis